2010
DOI: 10.1038/ja.2010.161
|View full text |Cite
|
Sign up to set email alerts
|

A novel class of geldanamycin derivatives as HCV replication inhibitors targeting on Hsp90: synthesis, structure–activity relationships and anti-HCV activity in GS4.3 replicon cells

Abstract: A novel class of geldanamycin (GA) derivatives as hepatitis C virus (HCV) replication inhibitors has been synthesized and their anti-HCV activities were evaluated in GS4.3 HCV replicon cells. Most of the synthesized compounds demonstrated potential activities against HCV in vitro. Substitution with an aliphatic cyclic group (2b) and polar phosphate group (2f) at the 17 position of GA resulted in more potent inhibitory activity. The configurations of the tetrahydrofurfurylamino (THFM) substituents obviously aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…22,23 Hsp90 is important for several virus replications and Hsp90 specific inhibitor GA blocks the replication of the viruses mentioned above in cell culture systems. [11][12][13][14][15][16][17][18][19] Most antiviral drugs in clinic use target a specific viral protein ensuring their specificity and limited toxicity. Though great progresses have been made through this approach, it is obvious that antiviral drugs targeting viral proteins have a relatively narrow antiviral spectrum and associate with the emergence of drug-resistant viral strains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22,23 Hsp90 is important for several virus replications and Hsp90 specific inhibitor GA blocks the replication of the viruses mentioned above in cell culture systems. [11][12][13][14][15][16][17][18][19] Most antiviral drugs in clinic use target a specific viral protein ensuring their specificity and limited toxicity. Though great progresses have been made through this approach, it is obvious that antiviral drugs targeting viral proteins have a relatively narrow antiviral spectrum and associate with the emergence of drug-resistant viral strains.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 GA exhibited antiviral activity in vitro was reported in many papers. [10][11][12][13][14][15][16][17][18][19] Relevant reports about antiviral activity of GA in vivo are relatively rare. We confirmed GA effectively inhibited HSV-1 in vivo in our previous work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2011, Shan et al 157 synthesized several GA analogues with substituent at C-17 position and/or C-19 position, 157 and found that most of the GA analogues with substituent at C-17 position showed similar magnitude of anti-HCV activity as compared to 63 with IC 50 s in the submicromolar range. However, these analogues also showed high toxicity toward the GS4.3 HCV replicon cells with SI values less than 10.…”
Section: Heat Shock Protein 90mentioning
confidence: 99%
“…[6] In our recent study, [7] we discovered that analogues of the marine alkaloid oroidin might prevent the replication of HCV through interaction with the cellular chaperone heat-shock protein 90 (Hsp90),p robably by binding to its ATP-binding site at the N-terminal domain. Characterized Hsp90 functions in HCV replication include interaction with HCV nonstructural proteins 5A and 5B, [10][11][12] enablingR NA replication, [13][14][15][16] maturation and stabilization of HCV proteins, [12,[17][18][19] translation of the viral genome, [20] and bypassing the cellular interferon responses. [8] The broad functions of Hsp90 cover numerousn ormal physiological processes, but are also essential under conditions of cellular stress.…”
Section: Introductionmentioning
confidence: 99%